Sagot :
Answer:
We have the equation,
x²+y²+2x+6y+9=0
When a circle is in this form we must complete the square in order to put in a usable format. like,
(x − a) 2 + ( y − b ) 2 = r2
where the centre is at ( a , b ) and radius is r.
So rearrange,
x 2 + x + y^2 - 6 y = − 9
And complete the square,
( x + 1/2 )^2 − 14 + ( y − 3 ) 2 − 9 = − 9
Rearrange;
( x + 1/2 )^2 + ( y − 3 ) 2 = 14
So from this equation, we know that our circle centre is at
( − 1/2 , 3 )
and the radius of our circle is,
√1/4 = 1/2
HOPE IT HELPS